Enzybiotic-mediated antimicrobial functionalization of polyhydroxyalkanoates - Blanco, Francisco G.; Vázquez, Roberto; Hernández-Arriaga, Ana M.; García, Pedro; Prieto, M. Auxiliadora (Frontiers in Bioengineering and Biotechnology, 2023)
Polymeric nanoparticles (NPs) present some ideal properties as biomedical nanocarriers for targeted drug delivery such as enhanced translocation through body barriers. Biopolymers, such as polyhydroxyalkanoates (PHAs) are gaining attention as nanocarrier biomaterials due to their inherent biocompatibility, biodegradability, and ability to be vehiculized through hydrophobic media, such as the lung surfactant (LS). Upon colonization of the lung alveoli, below the LS layer, Streptococcus pneumoniae, causes community-acquired pneumonia, a severe respiratory condition. In this work, we convert PHA NPs into an antimicrobial material by the immobilization of an enzybiotic, an antimicrobial enzyme, via a minimal PHA affinity tag. We first produced the fusion protein M711, comprising the minimized PHA affinity tag, MinP, and the enzybiotic Cpl-711, which specifically targets S. pneumoniae. Then, a PHA nanoparticulate suspension with adequate physicochemical properties for pulmonary delivery was formulated, and NPs were decorated with M711. Finally, we assessed the antipneumococcal activity of the nanosystem against planktonic and biofilm forms of S. pneumoniae. The resulting system displayed sustained antimicrobial activity against both, free and sessile cells, confirming that tag-mediated immobilization of enzybiotics on PHAs is a promising platform for bioactive antimicrobial functionalization.